If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(b + -4) = 2b + 8 Reorder the terms: -2(-4 + b) = 2b + 8 (-4 * -2 + b * -2) = 2b + 8 (8 + -2b) = 2b + 8 Reorder the terms: 8 + -2b = 8 + 2b Add '-8' to each side of the equation. 8 + -8 + -2b = 8 + -8 + 2b Combine like terms: 8 + -8 = 0 0 + -2b = 8 + -8 + 2b -2b = 8 + -8 + 2b Combine like terms: 8 + -8 = 0 -2b = 0 + 2b -2b = 2b Solving -2b = 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. -2b + -2b = 2b + -2b Combine like terms: -2b + -2b = -4b -4b = 2b + -2b Combine like terms: 2b + -2b = 0 -4b = 0 Divide each side by '-4'. b = 0 Simplifying b = 0
| -5(7x-12)+2(-6-10x)=-10x+3x | | (-2y^2)(4y)= | | z^2+3=4z | | -15x-1/3= | | z^2+3=3z | | q^2+19=20q | | 6x-3=4x+13 | | k/5.2+81.9=47.2 | | 14.5+x=6.2 | | x+15=-34 | | 4x^2-7=71 | | 2a^-1+3b^-2/a^-1-b^-1 | | x^4+14x^2+49= | | x^4-14x^2+49= | | (9x+7)(4x^2+5x+8)= | | -11(8p+4)=-11(p+11) | | -3x+2(-4)=10 | | 35p^6q^3/49p^6q^2 | | X+1/3x=36 | | 30/14=m/1.54 | | x^2+2x=26.01 | | 4(3x-4)=2(x-2) | | 9x-4=2(x+3) | | 3(5x-6)=-48 | | 4/3v-4/3 | | 26x+144x=0 | | 1/24*65^2=150 | | 14x-25x=9x | | -6(1x+5)=-72 | | -5.5x+0.56=-1.64 | | 1/24/65^2=150 | | 6x^2/3x^2=0 |